The use of Mentimeter as a medium for discussion in the EFL classroom: Students’ and teachers’ perspectives - Leonardho Jackly; Fransisca Endang Lestariningsih (Indonesian TESOL Journal, 2022)
This study investigates the extent of the use of Mentimeter interactive presentation software in classroom discussion, and examines the perspectives of students towards Mentimeter as discussion media. A qualitative method was applied in collecting data from the participants. Three students were interviewed regarding the extent of the use of Mentimeter and their perspective about Mentimeter as discussion media. The findings from the interview results show that Mentimeter is a versatile and simple app that can be utilised to support learning activity. Mentimeter is used mostly for elicitation activities, brainstorming, and for clarification during a lesson. The students acknowledge that the anonymity provided by Mentimeter makes them feel safer in participating in class discussion. In addition, this study could become a reference for teachers using and implementing Mentimeter in the classroom.     Keywords: Mentimeter, class discussions, interactive